1994
DOI: 10.1002/bit.260440916
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in nutrient‐deprived cultures of hybridoma and myeloma cells

Abstract: In the present study, cell death was investigated in cultures of NS/0 myelomas and SP2/0-derived D5 hybridomas through morphological examination of cells stained with acridine orange and ethidium bromide. The relative contribution of elevated levels of lactic acid and ammonia, as well as deprivation of glutamine, cystine, and glucose on the induction of necrosis or apoptosis, was investigated. In batch culture of D5 hybridoma cells, induction of apoptotic cell death correlated with the exhaustion of glutamine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
219
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(232 citation statements)
references
References 50 publications
13
219
0
Order By: Relevance
“…Amino acids considered essential for cellular proliferation were not always revealed as essential for survival, in particular glutamine. This discovery was in stark contrast to reports describing the induction of apoptosis in the absence of glutamine from the culture of many cell lines (Mecille and Massie 1994;Singh et al 1994;Simpson et al 1998;Sanfelui and Stephanopoulos 1999). Only cells that endogenously express GS synthetase or those genetically engineered to do so would be expected to survive such conditions as they are able to convert glutamic acid and ammonia to glutamine.…”
Section: Discussionmentioning
confidence: 65%
“…Amino acids considered essential for cellular proliferation were not always revealed as essential for survival, in particular glutamine. This discovery was in stark contrast to reports describing the induction of apoptosis in the absence of glutamine from the culture of many cell lines (Mecille and Massie 1994;Singh et al 1994;Simpson et al 1998;Sanfelui and Stephanopoulos 1999). Only cells that endogenously express GS synthetase or those genetically engineered to do so would be expected to survive such conditions as they are able to convert glutamic acid and ammonia to glutamine.…”
Section: Discussionmentioning
confidence: 65%
“…During this time, the degree of apoptosis remained at a basal level (less than 5%). However, nutrient concentrations continue to decrease and waste product levels began building up (Naderi et al 2010), both of which are potential triggers for apoptosis (Mercille and Massie 1994). The deterioration in extracellular conditions led to the initiation of apoptosis in cells after day 4.5.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient limitation, especially deprivation of glucose and amino acids, is one of the primary causes of cell death during the stationary and death phase of batch culture (Mercille and Massie 1994). Other possible causes of cell death include hyperoxia, hypoxia, and mechanical agitation in the hydrodynamic environment (Al-Rubeai and Singh 1998).…”
Section: Introductionmentioning
confidence: 99%
“…4). In an earlier study in which E1B-19K was expressed alone in an NS0 cell line, Mercille and Massie (1994) observed a correlation between expression level and apoptosis resistance, and the researchers also postulated that the activity would saturate at high levels of E1B-19K. Nivitchanyong et al (2007) found that there was a correlation of survival to E1B-19K expression level in BHK cells but only for the lower expressing cell lines.…”
Section: Expression Of Anti-apoptotic Genesmentioning
confidence: 99%
“…Inherent in current high density, protein-free mammalian cell cultures is the problem of cell death of which apoptosis can account for up to 80% in a typical fed-batch bioreactor, induced in response to insults such as nutrient and growth factor deprivation, oxygen depletion, toxin accumulation, and shear stress (Goswami et al, 1999). Apoptosis limits the maximum viable cell density, accelerates the onset of the death phase and potentially decreases heterologous protein yield (Chiang and Sisk, 2005;Figueroa et al, 2001Figueroa et al, , 2003Figueroa et al, , 2004Mastrangelo and Betenbaugh, 1998;Mercille and Massie, 1994).…”
Section: Introductionmentioning
confidence: 99%